Penolakan yang Digunakan dalam Film Drama dalam Bahasa Inggris - , RAHMATIKA, Aris Munandar, S.S., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research focuses on analyzing the statements spoken by the characters in drama movies in giving refusal. The objectives of this study are to find out the refusal strategies based on movies in english, describe how the variable of ages, status and familiarity are affecting the utterance in giving refusal, and to analyze the combination of speech acts which are used by the characters in the movies. The data used in this paper are selected randomly from American drama movies. The data were collected from 13 movies. The data were analyzed by Brown and Levinson theory of refusal strategies. The results of this research shows the different kinds of politeness strategies that are used by the characters in several American drama movies. The highest result from positive politeness strategy is Strategy 10, Offer and Promise. The first-highest result from negative politeness strategy is Strategy 3: Be Pessimistic, followed by Strategy 8: State the FTA as a general rule as the second-highest result.